Faces in the crowd : the Jews of Canada - Bialystok, Franklin (University of Toronto Press, 2022)
"The Jews were the first ethno-cultural minority to arrive in Canada, settling in Quebec in 1759. Their story is analogous to the experiences of subsequent immigrants as they arrived and settled into their new homes. Faces in the Crowd sheds light on the unique immigrant experience of the Jews in Canada by focusing on three processes: settlement, adaptation, and diversity. Drawing on case studies from the eighteenth century to the present day, Franklin Bialystok introduces the people and personalities who made up the Canadian Jewish experience. An appendix offers profiles of prominent individuals who have contributed to Canadian life since the Second World War, including business owners, rabbis, politicians, academics, writers, musicians, and entertainers. Exploring the immigrant experience through the lens of the collective, Bialystok adds new research, unique insights, and, best of all, memorable stories to the history of Jewish life in Canada."--